Penanganan Pengungsi Etnis Rohingya di Indonesia: Ditinjau Dari Perspektif Etika Sosial Islam Bercorak Kemaslahatan - ICHWANSYAH TAMPUBOLON (Fakultas Dakwah dan Ilmu Komunikasi, 2024)
This article is aims to describe the handling of refugees in Indonesia, especially in the case of Rohingya refugees from the perspective of Islamic social ethics in a descriptive-normative manner. The study takes the form of library research using a number of written reports in various state documents, online mass media reports, and interviews from television broadcast. Theoretically, the handling of refugees is carried out by referring to the ethical principle of public benefit (al-mashlahah al-`âmmah) by prioritizing humanitarian values and primary needs (al-mashlahah al-dharûriyyah). This is generally seen in terms of fulfilling the basic needs of refugees, especially in relation to the their interests of religion matters, life, and reason. Handling refugees involves cooperation parties between government, local communities and international social institutions.